Click, clack, moo : cows that type [book with audioplayer] - Cronin, Doreen (VOX Books., 2018)
Farmer Brown has a problem. His cows like to type. All day long he hears, click, clack, moo. Click, clack, moo. Click, clack, moo. But Farmer Brown's problems REALLY begin when his cows start leaving him notes.